Phase I study of TNFalpha AutoVaccIne in patients with metastatic cancer. - Waterston, A; Gumbrell, L; Bratt, T; Waller, S; Gustav-Aspland, J; L'hermenier, C; Bellenger, K; Campbell, M; Powles, T; Highley, M; Bower, M; Mouritsen, S; et al. (2005)
We evaluated the safety and immunogencity of a novel vaccine directed against autologous TNFalpha in a Phase I fixed dose escalation trial. The vaccine consisted of two recombinant TNFalpha proteins, with specific peptides replaced by foreign immunodominant T cell epitopes from tetanus toxoid. The main objectives were to establish a safe dose and evaluate the vaccines ability to raise neutralising TNFalpha antibodies. Secondary objectives were improvements in body weight and tumour response. Thirty-three patients were vaccinated with three doses (20, 100, or 400 mug) of TNFalpha vaccine at 2-weekly intervals adjuvanted with aluminium hydroxide. Anti-TNFalpha antibody titres were measured by both a RIA, using soluble native TNFalpha as the antigen, and by an ELISA using immobilized partly denatured TNFalpha. Eleven patients (33%) had mild grade1/2 injection site reactions at the higher doses. In 10 of 20 patients, serum antibodies recognize denatured TNFalpha in the ELISA, whereas, antibody titres against native TNFalpha in the RIA were undetectable. This suggests that the production process had partly denatured the vaccine preventing the formation of cross-reacting antibodies to native TNFalpha. In conclusion, TNFalpha vaccine was able to elicit vaccine specific antibodies. However, since the antibodies were only able to cross-react with partly denatured TNFalpha, evaluation of safety and tumour responses to the TNFalpha vaccine was compromised.